Rapid detection for infected ascites in cirrhosis using metagenome next‐generation sequencing: A case series. (22nd November 2021) - Li, Beiling; He, Qinjun; Rui, Yongyu; Chen, Yan; Jalan, Rajiv; Chen, Jinjun
Abstract: Empirical antibiotic therapy in patients with spontaneous bacterial peritonitis (SBP) is common as pathogen(s) are identified in only 5%‐20% patients using conventional culture‐based techniques. Metagenome next‐generation sequencing (mNGS) test is a promising approach for the diagnosis of infectious disease. The clinical application of mNGS for infected ascites in cirrhotic patients is rarely reported. Here, we describe three cases to preliminarily explore the potential role of mNGS for microbiological diagnosis of ascites infection in an exploratory manner. The clinical performance of ascites mNGS in cirrhotic patients remains to be further evaluated.